Oral ulcers in a finger‐sucking child after cutaneous wart therapy. Issue 6 (14th October 2021) - McConnell, Jennifer; Epperson, Lindsey Claire; Eifert, Faye; Aldy, Kim
Abstract: Common skin warts frequently appear on the fingers of children, a patient population in whom finger‐sucking is a prevalent habit. Despite overlap between these two pediatric conditions, there are no well‐reported specific precautions against the use of topical blistering wart treatments, such as trichloroacetic acid and cantharidin, in finger‐sucking children with warts. We report the case of oral ulcers in a pediatric patient secondary to thumb‐sucking after receiving treatment for multiple finger warts with combination cryotherapy, trichloroacetic acid, and cantharidin.